T helper type 1‐related molecules as well as interleukin‐15 are hyperexpressed in the skin lesions of patients with pyoderma gangrenosum. (23rd June 2017) - Antiga, E.; Maglie, R.; Volpi, W.; Bianchi, B.; Berti, E.; Marzano, A. V.; Caproni, M.
Summary: Pyoderma gangrenosum (PG) is a rare, immune‐mediated skin disease classified into the group of neutrophilic dermatoses. Although a number of studies confirmed the central role of innate immunity, only few studies have investigated the possible contributing role of acquired immunity. In particular, no reports concerning T helper type 1 (Th1) and Th2 cells are available as yet. Therefore, 15 patients with PG, five with Sweet's syndrome (SS) and nine skin specimens from healthy controls (HC) were investigated, evaluating the expression of Th1‐related markers interleukin (IL)‐12, interferon (IFN)‐γ, C‐X‐C motif chemokine receptor 3 (CXCR3) and C‐C motif chemokine receptor 5 (CCR5), of the Th2‐related molecules IL‐4, IL‐5, IL‐13 and CCR3, of the co‐stimulatory axis CD40/CD40 ligand, of IL‐15 and the natural killer (NK) cell marker CD56 in skin lesions by immunohistochemistry. Patients with PG and SS showed a higher expression of Th1 markers than HC. Conversely, IL‐5‐ and CCR3‐expressing cells were less numerous in PG skin lesions compared to SS ( P = 0·0157 and < 0·0001, respectively). Both CD40 and CD40L were expressed more in PG than in SS and HC ( P < 0·0001 for both). Finally, the number of IL‐15 + and CD56 + cells was higher in the skin of patients with PG than in those of SS and HC ( P < 0·0001 for both). Our results suggest that Th2 cells are down‐regulated in PG. At the same time, over‐expression of the co‐stimulatory axis CD40/CD40L amplifies the impairment of the Th1/Th2 balance. Both these findings might explain the most aggressive behaviour of PG in comparison to SS. Moreover, over‐expression of IL‐15 + and CD56 + cells may suggest a possible role of NK cells in the pathogenesis of the disease. Abstract : Pyoderma gangrenosum (PG) is a rare, immune‐mediated skin disease classified into the group of neutrophilic dermatoses. Our results suggested that Th1 cells are increased while Th2 cells are downregulated in PG. Moreover, the overexpression of the co‐stimulatory axis CD40/CD40L amplifies the impairment of the Th1/Th2 balance and NK cells that are recruited with an IL‐15 mediated signal, may contribute to the development of the skin damage.